C-Reactive Protein and Cancer—Diagnostic and Therapeutic Insights - Hart, Peter C.; Rajab, Ibraheem M.; Alebraheem, May; Potempa, Lawrence A. (Frontiers in Immunology, 2020)
Cancer disease describes any pathology involving uncontrolled cell growth. As cells duplicate, they can remain localized in defined tissues, forming tumor masses and altering their microenvironmental niche, or they can disseminate throughout the body in a metastatic process affecting multiple tissues and organs. As tumors grow and metastasize, they affect normal tissue integrity and homeostasis which signals the body to trigger the acute phase inflammatory response. C-reactive protein (CRP) is a predominant protein of the acute phase response; its blood levels have long been used as a minimally invasive index of any ongoing inflammatory response, including that occurring in cancer. Its diagnostic significance in assessing disease progression or remission, however, remains undefined. By considering the recent understanding that CRP exists in multiple isoforms with distinct biological activities, a unified model is advanced that describes the relevance of CRP as a mediator of host defense responses in cancer. CRP in its monomeric, modified isoform (mCRP) modulates inflammatory responses by inserting into activated cell membranes and stimulating platelet and leukocyte responses associated with acute phase responses to tumor growth. It also binds components of the extracellular matrix in involved tissues. Conversely, CRP in its pentameric isoform (pCRP), which is the form quantified in diagnostic measurements of CRP, is notably less bioactive with weak anti-inflammatory bioactivity. Its accumulation in blood is associated with a continuous, low-level inflammatory response and is indicative of unresolved and advancing disease, as occurs in cancer. Herein, a novel interpretation of the diagnostic utility of CRP is presented accounting for the unique properties of the CRP isoforms in the context of the developing pro-metastatic tumor microenvironment.